(untitled) (Global Journal of Human-Social Science, 2024)
We started from the observation that the CEMAC countries have presented a very high level of military spending over the past two decades As a result we have set ourselves the objective of analyzing the link between non-renewable natural resources and the evolution of military spending within the Economic and Monetary Community of Central Africa CEMAC from 2000 to 2020 To do this we performed the Hausman specification test and selected the fixed effect econometric model The result of the estimation of this model showed that non renewable natural resources positively and weakly affect military expenditure in the CEMAC zone through a positive and significant effect of mining and oil rents In view of these results we recommended that public decisionmakers put in place a procedure to allocate budgetary resources to military services according to clear and measurable objectives through mechanisms to verify the achievement of objectives against the resources devoted to them